Client’s Communication Privacy Boundaries in Ruang Refleksi Online Service of Halo Jiwa Indonesia - Andi Bulqis Safirah; Tuti Bahfiarti; Jeanny Maria Fatimah (LONTAR: Jurnal Ilmu Komunikasi, 2025)
Ruang Refleksi Online (RRO), or Online Reflection Room, is one of Halo Jiwa Indonesia’s online-based counseling services, providing emotional support to people since the COVID-19 pandemic. This online-based counseling is a free and non-professional service provided by peer counselors from Halo Jiwa Indonesia members, which was held in 2020. This study aims to know how the client manages their privacy rules in peer counseling, according to five criteria of Communication Privacy Management in boundary rules, which are culture, motivation, context, gender, and risk-benefit ratio. This research type is a qualitative method with a case study approach. Four clients were chosen from purposive sampling with a specific category. From this study, it can be concluded that clients of Ruang Refleksi Online created their privacy rule according to their motivation, contextual, and risk-benefit ratio factors. This determines how much self-disclosure they can share with the peer counselor during interpersonal communication in the counseling session. The clients could also feel the positive impact, such as feeling calmer and relieved from Ruang Refleksi Online